Economic and Mathematical Modeling in Budgeting - Latysheva, O.; Chupryna, Yu. (Економічний вісник Донбасу, 2023)
The article is devoted to an overview of modern modeling approaches for effective management of enterprise budgets. The article examines the toolkit of economic and mathematical modeling that can be used in the budgeting system. It is proposed to increase the efficiency of the budgeting process by applying the tools of economic and mathematical modeling at the stages of budget development and resource allocation, as well as in the process of budget control and monitoring. To increase the clarity of the simulation procedure and results, a visualization of the TO BE model is presented in IDF0 notation (simulation language) on the Ramus platform.
It is noted that the effectiveness of the budgeting system based on the use of economic-mathematical modeling tools will allow to improve resource expenditure planning taking into account the opportunities, priorities, needs and limitations of a specific enterprise and its external business environment. The need to implement digitalization tools and economic-mathematical modeling in the budgeting system is substantiated.
The purpose of the article is to analyze the possibilities of forming an effective enterprise budgeting system based on the successful implementation of economic and mathematical modeling tools. The authors focus on the potential of using business analytics as a result of using economic and mathematical modeling tools to form an effective budgeting system.
The article argues for the possibility of effectively using modeling tools in the budgeting process, which allows enterprises to make high-quality management decisions based on forecasts, scenarios, optimization recommendations, visualization of current problem situations, etc.
The scientific novelty of this article lies in the fact that the recommendations and conclusions provided by the authors can be useful for domestic enterprises in the current conditions of severe restrictions on available resources, lack of free funds, existing and potential risks. In general, this article is useful for those who want to learn more about the possibilities of using economic-mathematical modeling tools in the budgeting system. Стаття присвячена огляду сучасних підходів моделювання для ефективного управління бюджетами підприємства. У статті досліджено інструментарій економіко-математичного моделювання, який може застосовуватися в системі бюджетування. Запропоновано підвищити ефективність процесу бюджетування шляхом застосування інструментарію економіко-математичного моделювання на стадіях розробки бюджету та розподілу ресурсів, а також у процесі бюджетного контролю та моніторингу. Для підвищення наочності процедури та результатів моделювання представлена візуалізація моделі TO BE в нотації (мові моделювання) IDF0 на платформі «Ramus».
Зазначено, що ефективність системи бюджетування на підставі використання інструментарію економіко-математичного моделювання дозволить покращити планування витрат ресурсів з урахуванням можливостей, пріоритетів, потреб та обмежень конкретного підприємства та його зовнішнього бізнес - середовища. Обґрунтовано необхідність впроваджувати інструментарій діджиталізації та економіко-математичного моделювання в системі бюджетування.
Метою статті є аналіз можливостей формування дійової системи бюджетування підприємств на підставі успішної імплементації інструментарію економіко-математичного моделювання.
Автори орієнтуються на потенціал використання бізнес-аналітики як результату використання інструментарію економіко-математичного моделювання для формування ефективної системи бюджетування.
У статті аргументовано можливості ефективного використовувати інструментарію моделювання у процесі бюджетування, що дозволяє підприємствам приймати якісні управлінські рішення на підставі прогнозів, сценаріїв, рекомендацій оптимізації, візуалізації поточних проблемних ситуацій тощо.
Наукова новизна даної статті полягає в тому, що рекомендації та висновки, надані авторами, можуть стати корисними для вітчизняних підприємств в існуючих умовах жорстких обмежень наявних ресурсів, нестачі вільних коштів, існуючих та потенційних ризиків. Загалом, ця стаття є корисною для тих, хто бажає більш детально ознайомитися з можливостями використання інструментарію економіко-математичного моделювання в системі бюджетування.